2017
DOI: 10.1002/macp.201770067
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Chem. Phys. 21/2017

Abstract: Front Cover: Self‐assembly of microgels is an efficient strategy of constructing intelligent material but reversible self‐assembly of microgels remains a challenge. Utilizing the light‐responsive host–guest interaction between an azobenzene‐nanogel and an α‐cyclodextrin microgel, Ping Wang, Qiaofeng Yang, Zhipeng Ye, Chuanzhuang Zhao,* and Jingfa Yang in article number https://doi.org/10.1002/macp.201700280 propose a facile method to realize the assembly/disassembly of soft colloids with light stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As previously mentioned, the fluorescence of stilbene-maleic anhydride alternating copolymer was reported in 1975. [58] In that study, the copolymer solution in dioxane was irradiated at 260 nm, and fluorescence emission peaks at 285 nm, and 320-360 nm were observed, which corresponds to the phenyl ring emission and excimer emission, respectively. Studies on the fluorescent properties of α, ω-diphenylalkanes showed that it is necessary to have at least three atoms between two phenyl rings in order to form excimers.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As previously mentioned, the fluorescence of stilbene-maleic anhydride alternating copolymer was reported in 1975. [58] In that study, the copolymer solution in dioxane was irradiated at 260 nm, and fluorescence emission peaks at 285 nm, and 320-360 nm were observed, which corresponds to the phenyl ring emission and excimer emission, respectively. Studies on the fluorescent properties of α, ω-diphenylalkanes showed that it is necessary to have at least three atoms between two phenyl rings in order to form excimers.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies on the fluorescence of maleic anhydride or maleimide-containing polymers attributed the fluorescence to clustering of the locked carbonyl groups or the "space conjugate" of the carbonyl and the neighboring phenyl groups. [26,34,36,58] For our alternating copolymers, it is likely that the fluorescence of 330 nm irradiation also comes from the π-π interactions between the phenyl rings and CO groups from the anhydride groups through space. We used density functional theory (DFT) to calculate the molecular orbitals in order to find out if the fluorescence of the alternating copolymers can also result from the "space conjugate."…”
Section: Resultsmentioning
confidence: 97%
“…Micro-solvation details around such polyatomic ions are of fundamental interests, and recent spectroscopic studies have shed considerable lights into the geometry, electronic structures, and dynamics in such hydrated cluster ions. 1523 Particularly relevant to HSO 4 − (H 2 O) n are the recent studies on H 2 PO 4 − (H 2 O) n and HCO 3 − (H 2 O) n . 2428 All three singly charged anions have two kinds of groups, X=O and XOH, with the XO stretching ( υ (X=O)) and the XOH bending ( δ (XOH)) coupled together with considerable overlap.…”
Section: Introductionmentioning
confidence: 99%
“…However, PUF is prone to cracking reaction at high temperature and presents poor heat resistance due to thermally unstable groups on its molecules, such as urea, allophanate, carbamate and biuret. Usually, its long‐term service temperature is below 85 °C, while it can be used between 80 and 100 °C for only a few days, maintaining its mechanical properties without obvious deterioration at 120 °C for only a few hours, and serious thermal degradation quickly occurs above 200 °C. As a result, the processing or application of PUF is restricted in high temperature environments.…”
Section: Introductionmentioning
confidence: 99%